Immunohistochemical Expression of Ki67 and HER2/neu in Urothelial Tumors - Tyagi, Niketa; Agarwal, Deepti; Kaur, Swaran; Khandelwal, Atul (Annals of Pathology and Laboratory Medicine, 2025)
Background: Urinary bladder cancer is the most common malignancy involving the urinary system and the ninth most common malignancy worldwide. Proliferation marker kinase inhibitor (Ki67) is a nuclear and nucleolar non-histone DNA-binding protein that is encoded by the MKi67 gene in humans. Human epidermal growth factor receptor 2 (HER2) is a transmembrane tyrosine kinase receptor that is involved in cellular growth, survival, and migration. Materials and Methods: The cross-sectional study was conducted for the duration of one year in the Department of Pathology, BPS Medical College for Women, Khanpur Kalan, Sonepat. Tissue sections, after proper processing, were stained with haematoxylin and eosin. A total of 50 histopathologically proven cases of urothelial tumors were included in the study. Correlation of urothelial tumors was studied with age, gender, smoking, and tumor grading. Urothelial tumors were classified according to the WHO classification of tumors of the urinary bladder (2016), and IHC markers Ki67 and HER2/neu expressions were evaluated. Results: Among 50 cases of urothelial tumors, 25 (50%) cases were low-grade urothelial carcinoma, followed by 22 (44%) cases of high-grade urothelial carcinoma. Two cases of squamous cell carcinoma and one case of papillary urothelial neoplasm of low malignant potential were also observed. Ki67 expression was significantly associated with urothelial carcinoma (p-value = 0.01). HER2/neu expression showed a significant association with muscle-invasive tumors (p-value = 0.02). Conclusion: Positive Ki67 and HER2/neu expression correlated with tumor grade. Assessing HER2/neu status could identify patients with high-grade disease who might benefit from adjuvant HER2/neu treatment after radical cystectomy.